Efficacy of phytoseiid mites and pesticides to control Bemisia tabaci, Thrips tabaci and Tetranychus urticae on Capsicum annuum - Marwa Barghout; Samar Ibrahim; El‑Sayed El‑Saiedy (Persian Journal of Acarology)
Four predatory mites including Amblyseius swirskii, Cydnoseius negevi, Neoseiulus cucumeris, and Phytoseiulus persimilis, as well as mixture of commercial pesticides named Actara® and Egyxide® (Emulsified vegetable oil) were used to manage the population of Bemisia tabaci, Thrips tabaci, and Tetranychus urticae on red delta star pepper cultivar of Capsicum annuum. All treatments were applied separately and in combination on pepper cultivar grown in a high plastic-net tunnel. The results showed that A. swirskii released separately or combined with other treatments significantly suppressed the population of B. tabaci and T. tabaci to 0.00 and 0.04–2.10 individual/leaf, respectively. Cydnoseius negevi and N. cucumeris significantly reduced B. tabaci population. However, the latter was the most effective against T. tabaci. The numerical densities of movable and egg stages of T. urticae reduced significantly by P. persimilis alone or along with A. swirskii, followed by the release of A. swirskii with N. cucumeris and reached 0.00 individual/leaf. The most effective treatments for T. tabaci with percent reduction ranging from 94.53% to 100% were A. swirskii, N. cucumeris, and all combined treatments. Treatments with pesticides, C. negevi, and A. swirskii + pesticides exhibited less efficiency in controlling B. tabaci, T. tabaci, and T. urticae, respectively. Our findings indicated that the applied bio-agents were efficient, and the inclusion of A. swirskii in programs of integrated pest management is advisable for controlling B. tabaci, T. tabaci, and T. urticae on the pepper cultivar.